1974
DOI: 10.1093/jn/104.7.957
|View full text |Cite
|
Sign up to set email alerts
|

On the Repression of Rat Liver HMP Shunt Dehydrogenases by Wheat Gluten

Abstract: The liver levels of HMP shunt dehydrogenases were determined in adult male rats fed for 6 days, after a 6-day protein deprivation, diets containing as their nitrogenous components wheat gluten, or casein or amino acid mixtures simulating the amino acid pattern of these proteins. The gluten diet, in comparison to the casein diet, caused lower activities of HMP shunt dehydrogenases. Amino acid diets failed to display the differential effect observed with the protein diets. The gluten diet, compared to the casein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1975
1975
1976
1976

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In table 3 the levels of plasma insulin are shown. As has previously been found (21)(22)(23)(24), rats fed the gluten diet for 6 days had lower body weight gain, smaller liver and less liver protein than rats fed the casein diet. These effects were overcome by adding a suffi cient amount of Lys and Thr to the gluten.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…In table 3 the levels of plasma insulin are shown. As has previously been found (21)(22)(23)(24), rats fed the gluten diet for 6 days had lower body weight gain, smaller liver and less liver protein than rats fed the casein diet. These effects were overcome by adding a suffi cient amount of Lys and Thr to the gluten.…”
Section: Resultssupporting
confidence: 81%
“…In our previous studies of the effect of dietary protein on the response of HMPD we have shown that in rats fed a gluten diet, the HMPD activity did not reach the level found in the rats fed the casein diet. This effect was independent of both the amino acid composition of the gluten and of its essential fatty acids content (21)(22)(23)(24)(25).…”
mentioning
confidence: 99%